Development of Conductive Electrospun Fabric Systems for Smart Textiles - Perdigão, Patrícia Filipa Vieira Pereira da Rocha (2018)
Electrospinning (ES) is a simple, cost-effective and versatile method for the production of nanofibrous materials. However, the production of intrinsically conductive polymers (ICPs) nan-ofibres by electrospinning still represents an important challenge – often due to poor solubility and high crystallinity of the rigid backbone. This dissertation reports the development of conductive fibres produced by electrospinning of two ICPs: polyaniline (PANI) and poly(3,4-ethylenedioxythiophene)-poly(styrenesulfonate) (PEDOT:PSS). These were electrospun and studied in terms of their electrical conductivity. In both cases, polyvynilpyrrolidone (PVP) was used as a carrier polymer in the ES process. PANI was synthesised from the aniline monomer and the influence of the oxidant-to-mon-omer ratio on its conductivity was studied. Pellets of pressed PANI powders resulted in an average conductivity of 20.64 S.cm-1. The chemical addition of a tert-butyloxycarbonyl (t-Boc) group to the structure of PANI allowed the dissolution in dimethylformamide (DMF). The soluble PVP/t-Boc-PANI was electrospun into fibres with an average fibre diameter of 180 nm with a maximum conductivity of 5.1810-3 S.cm-1. Electrospinning of PVP/PEDOT:PSS allowed the production of non-woven mats with an average fibre diameter of 1.5 μm with a conductivity of 4.010-8 S.cm-1. A thorough study of the UV crosslinking of PVP is enclosed.